Distribution of Federal and State Income Taxes by Income Classes - Pechman, Joseph A. (Journal of Finance, 1972)
Joseph A. Pechman, Distribution of Federal and State Income Taxes by Income Classes, The Journal of Finance, Vol. 27, No. 2, Papers and Proceedings of the Thirtieth Annual Meeting of the American Finance Association, New Orleans, Louisiana, December 27-29, 1971 (May, 1972), pp. 179-191